Family Involvement in Strengthening Character Education: Integrating Sundanese Values and the Merdeka Curriculum - Jamaluddin Jamaluddin; Ahmad Sukandar (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to analyze family involvement in strengthening character education through the integration of Sundanese cultural values within the implementation of the Merdeka Curriculum at SDN 2 Cibodas, Cimahi City. Using a descriptive qualitative approach and an intrinsic case study design, the research involved four months of participant observation, in-depth interviews with 15 parents, 6 teachers, and 10 students, as well as document analysis from school and community sources. The findings reveal that family involvement in character education remains limited due to economic constraints—41.2% of parents earn IDR 1–2 million per month—and long working hours, resulting in a 34% rate of student indiscipline. Sundanese values such as silih asih, silih asah, and silih asuh serve as moral anchors but have declined by 40% due to digital media exposure. The integration of the Merdeka Curriculum through the Pancasila Student Profile Strengthening Project offers an opportunity to revitalize local wisdom via a hybrid collaboration model between families and schools. Theoretically, this study extends Bronfenbrenner’s Ecological Theory by incorporating digital literacy and school infrastructure as mediating variables, while practically proposing a local-culture-based family–school synergy model to reinforce students’ character development in urban settings